Partial Sequencing of 16S rRNA Gene of Selected Staphylococcus aureus Isolates and its Antibiotic Resistance - Harsi Dewantari Kusumaningrum; Lita Handayani; Reni Nofrianti (Media Peternakan, 2016)
The choice of primer used in 16S rRNA sequencing for identification of Staphylococcus species found in food is important. This study aimed to characterize Staphylococcus aureus isolates by partial sequencing based on 16S rRNA gene employing primers 16sF, 63F or 1387R. The isolates were isolated from milk, egg dishes and chicken dishes and selected based on the presence of sea gene that responsible for formation of enterotoxin-A. Antibiotic susceptibility of the isolates towards six antibiotics was also tested. The use of 16sF resulted generally in higher identity percentage and query coverage compared to the sequencing by 63F or 1387R. BLAST results of all isolates, sequenced by 16sF, showed 99% homology to complete genome of four S. aureus strains, with different characteristics on enterotoxin production and antibiotic resistance. Considering that all isolates were carrying sea gene, indicated by the occurence of 120 bp amplicon after PCR amplification using primer SEA1/SEA2,  the isolates were most in agreeing to S. aureus subsp. aureus ST288. This study indicated that 4 out of 8 selected isolates were resistant towards streptomycin. The 16S rRNA gene sequencing using 16sF is useful for identification of S. aureus. However, additional analysis such as PCR employing specific gene target, should give a valuable supplementary information, when specific characteristic is expected.